The Dynamics of Competency-Based Curriculum Implementation: A Mixed-Methods Study at SMK Negeri 2 Tenggarong - Tambunan, Audi Aryna; Haeruddin, Haeruddin; Akhmad, Akhmad (Ridwan Institute, 2025)
Amidst the rapid development of the Industrial Revolution 4.0 and the acceleration of digitalization, Vocational High Schools in Indonesia face important challenges in preparing graduates who are skilled, flexible, and ready to enter the ever-changing world of work. This research aims to analyze the implementation of the Competency-Based Curriculum (CBC) at SMK Negeri 2 Tenggarong through the Total Quality Management (TQM) approach and the integration of the link-and-match concept with the industrial sector. Using a mixed-methods approach, quantitative data was collected from 67 teachers through questionnaires, while qualitative data was gathered through semi-structured interviews with 8 key informants. The results indicate that teachers' understanding of the CBC concept is classified as very good, but its implementation still faces challenges in training, infrastructure, and industrial partnerships. The transformational leadership of the school principal and the application of the PDCA cycle have been shown to play a vital role in driving continuous improvement. Furthermore, the limitations of facilities and the lack of optimal industrial involvement in curriculum planning are the main obstacles.